The Influence of Art Therapy in Counseling: Enhancing Psychological Wellbeing - Dina Ahmed; Mai Kamal; Rasha Al-Ansari (Research Psychologie, Orientation et Conseil, 2025)
Psychological well-being is a critical factor influencing overall mental health, yet traditional counseling approaches may not fully address the diverse needs of clients. Art therapy, as a creative and expressive intervention, has gained recognition for its potential to enhance psychological well-being through non-verbal and experiential processes. This study investigates the influence of art therapy in counseling and its effectiveness in promoting psychological well-being. The research aimed to evaluate the impact of art therapy on emotional regulation, self-awareness, and stress reduction among individuals seeking counseling services. A mixed-methods design was employed, combining quantitative and qualitative approaches. A total of 80 participants were divided into intervention and control groups, with the intervention group attending a 10-week art therapy program integrated into their counseling sessions. Data were collected through standardized psychological well-being scales and semi-structured interviews. Results indicated significant improvements in psychological well-being scores for the intervention group compared to the control group (p < 0.01). Participants reported increased emotional expression, enhanced coping mechanisms, and a stronger sense of self-awareness. Qualitative data supported these findings, highlighting art therapy’s role in fostering a safe and reflective space for personal growth. The study concludes that art therapy is an effective complementary approach in counseling, offering valuable benefits for enhancing psychological well-being. These findings underscore the importance of integrating creative methods into therapeutic practices.